PENGARUH PARTISIPASI PEMAKAI DAN KETIDAKPASTIAN TUGAS PADA KINERJA SIA DENGAN UKURAN ORGANISASI SEBAGAI VARIABEL MODERASI - Kurniawati, Ni Putu Ayu Yuni; Dwirandra, A.A.N.B. (E-Jurnal Akuntansi, 2017)
This purpose of this research was to prove empirically the effect of user participation and uncertainty tasks on accounting information system performance with organization size as moderating variable. Research was done in LPD in Ubud districts. Sample selection is done by using a sampling method saturated with total respondents 86 people consisting of Chief LPD, cashier, and accounting. The analysis technique used is multiple linear regression analysis and Moderated Regression Analysis (MRA). The results indicated that: 1) user participation  positively effect toward accounting information system performance in LPD Ubud districts, 2) uncertainty tasks negatively effect toward accounting information system performance in LPD Ubud districts, 3) organization size is able to moderate the impact of user participation on accounting information system performance in LPD Ubud district, and 4) organization size is not able to moderate the impact of uncertainty tasks on accounting information system performance in LPD Ubud district.
Keywords: user participation, uncertainty tasks, organization size, accounting information system performance